The space of literary tastes of Belarusian readers: sociological aspect - Belski, Alexander M. (Journal of the Belarusian State University. Sociology, 2024)
The results of a representative sociological study of reading preferences of the population of the Republic of Belarus are presented. The dependence of the literary tastes of Belarusians on such predictors as level of education and sexual identity is analysed. The space of literary preferences of respondents is graphically presented. It has been established that women demonstrate greater awareness of Belarusian novelists and poets than men. In addition, the higher the level of education of a Belarusian, the higher the likelihood that he is interested in the work of contemporary Belarusian authors.
Keywords: literary preferences; elite culture; level of education; sexual identuty; sociology of culture